2020
DOI: 10.1080/13562576.2020.1773779
|View full text |Cite
|
Sign up to set email alerts
|

Paddison electoral and fiscal geographies

Abstract: Electoral geographies I: maps and power…I well remember a conversation I had, as a callow final year undergraduate, with Ronan during the 1983 UK General Election campaign. The conversation took placeas was common thenin the pub after, if memory serves, a meeting of the Glasgow University Geographical Society (who was giving that evening's lecture, and what it was on, are sadly lost in the mists of time: reader, if you were the speaker, I apologise!). I fancied myself as a bit of a radical, and was holding for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This 1976-1977 issue also saw the first glimpse of what Ronan was beginning to bring to Glasgow Geography: positioned in the 'Jogsok Top Ten' (as in musical 'chart hits'), 'Ronan and the Hot Rods' were performing 'You're More than a Number' (Drumlin, 1976b, n.p. : 'Jogsok' being the Student Geographical Society), the likely implication being that Ronan was emphasising to students the deficiencies of a purely quantitative approach to geographical study, notwithstanding his own statistical capacities as reported in this issue by Pattie (2020). Subsequently, as I will show, sightings of Ronan in Drumlin tended to be fuller and open to much more 'interpretation', such as in the article 'Focus on Ronan Paddison' (Drumlin, 1983, n.p.…”
Section: Ronan From the Pages Of Drumlinmentioning
confidence: 91%
See 2 more Smart Citations
“…This 1976-1977 issue also saw the first glimpse of what Ronan was beginning to bring to Glasgow Geography: positioned in the 'Jogsok Top Ten' (as in musical 'chart hits'), 'Ronan and the Hot Rods' were performing 'You're More than a Number' (Drumlin, 1976b, n.p. : 'Jogsok' being the Student Geographical Society), the likely implication being that Ronan was emphasising to students the deficiencies of a purely quantitative approach to geographical study, notwithstanding his own statistical capacities as reported in this issue by Pattie (2020). Subsequently, as I will show, sightings of Ronan in Drumlin tended to be fuller and open to much more 'interpretation', such as in the article 'Focus on Ronan Paddison' (Drumlin, 1983, n.p.…”
Section: Ronan From the Pages Of Drumlinmentioning
confidence: 91%
“…(Paddison, 1982, p. 15) A host of theoretical-historiographic considerations permeate this passage, demonstrating Ronan's familiarity with older disciplinary approaches: regional description, locational analysis (identified here, with great acuity, as 'the geometry of social relations') and engaging Peet's own rejection of quantitative geography, behavioural geography, humanistic geography (enmired in 'the intricacies of human experience') and also the 'liberal' or 'welfare geography' tradition closely associated in the UK with David M. Smith (the target, I suggest, when Peet was attacking 'vague moral humanism': see Smith, 1977Smith, , 1979. Ronan's reflection has a tone that suggested his distaste for such crude dismissals of other, non-Marxist endeavours, past and present, andas in the quote belowhe confessed his own training in behaviouralism (and note the behavioural bent to a political geography textbook that Ronan co-authored: as well as quantification (see also Pattie, 2020). He noted how Marxist geography set up camp in opposition to behaviouralism -'one of the bète-noirs of the radical' (Paddison, 1982, p. 15)and also to humanistic geography, yet Ronan supposed that these more human-facing positions should still be valued for 'the understanding they give of man [humanity] in space' (Paddison, 1982, p. 15).…”
Section: The Peet-paddison Exchangementioning
confidence: 99%
See 1 more Smart Citation